2018
DOI: 10.1093/mmy/myy013
|View full text |Cite
|
Sign up to set email alerts
|

Melanin: Quantification and protection against oxidative stress in chromoblastomycosis agents

Abstract: Chromoblastomycosis (CBM) is a chronic cutaneous and subcutaneous infection caused by melanized fungal species. We quantified the extractable melanin of 77 strains of CBM agents distributed within five genera. Moreover, resistance to oxidative stress was evaluated in strains exposed or not to the melanin inhibitor tricyclazole. The median percentage of melanin mass extracted from dry fungal mass varied from 0.69 (Rhinocladiella similis) to 3.81 (Phialophora americana). Inhibition of melanin synthesis decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…To determine whether the process of melanization elicits changes in cell-wall composition, we examined cells from the three strains, each grown in the presence and absence of L-DOPA. Since melanin pigments have been reported previously to comprise only a minor fraction (1–15.4%) of the total dry mass of melanizing fungal cells [ 50 , 51 ] and are likely to have large molar masses, the NMR signals that arise from pigment carbons make a negligible contribution to the overall spectral intensity. Consequently, we were able to make quantitative estimates of relative polysaccharide content regardless of whether melanin was present.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the process of melanization elicits changes in cell-wall composition, we examined cells from the three strains, each grown in the presence and absence of L-DOPA. Since melanin pigments have been reported previously to comprise only a minor fraction (1–15.4%) of the total dry mass of melanizing fungal cells [ 50 , 51 ] and are likely to have large molar masses, the NMR signals that arise from pigment carbons make a negligible contribution to the overall spectral intensity. Consequently, we were able to make quantitative estimates of relative polysaccharide content regardless of whether melanin was present.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the process of melanization elicits changes in cell-wall composition, we examined cells from the three strains, each grown in the presence and absence of L-DOPA. Since melanin pigments have been reported previously to comprise only a minor fraction (1-15.4%) of the total dry mass of melanizing fungal cells (44,45) and are likely to have large molar masses, the NMR signals that arise from pigment carbons make a negligible contribution to the overall spectral intensity. Consequently, we were able to make quantitative estimates of relative polysaccharide content regardless of whether melanin was present.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that gravimetric analysis is adequate to quantify DHN‐melanin, as the small expected result in the condition of hypopigmentation has been achieved [9]. This same method was used by Heidrich et al [34], who carried out a study with the five main genera of CBM agents. In this study, the average percentage of melanin mass extracted from the dry fungal with mass ranged from 0.69% ( Rhinocladiella similis ) to 3.81% ( Phialophora americana ), showing that its quantification is variable among the main fungi that cause CBM.…”
Section: Qualitative and Quantitative Analysismentioning
confidence: 99%
“…In a more comprehensive study, conducted in 2018 with 77 strains of CBM agents, distributed in five different genera, it was found that melanin conferred protection against oxidative stress in all isolates. In general, the degree of protection was proportional to the amount of melanin that each species produces, however it is possible that there are other protective factors in addition to this compound [34].…”
Section: Structural and Antioxidant Functionsmentioning
confidence: 99%